SOLUTIONS OF FORWARD PROBLEMS OBTAINED VIA BOUNDARY ELEMENT METHOD FOR NONHOMOGENEOUS DOMAINS IN REGARD TO ELECTRICAL CONDUCTIVITY - Tchórzewski, Paweł (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2019)
I present solution of the forward problem for electric field obtained through the boundary element method. The function which describes electrical conductivity distribution on the domain possesses two different nonzero values. Proposed approach can be utilised in order to obtain solution of the inverse problem in the flood embankment control system. Such system relies on the electrical impedance tomography.